Preventing Sexual Violence Against Women Through the Short Film 'Demi Nama Baik?' - Suryani, Riri Irma; Purnamasari, Dwi Candra; Linda, Gusnita (Universitas Multimedia Nusantara, 2023)
Sexual violence cannot be ignored. Sexual violence can happen to anyone, be it children, teenagers, adults, men or women. One of the things that can be done to prevent sexual violence can be done using film media. The production of a short film with the title “Demi Nama Baik?” with the hashtag #Don’t Just Shut Up” is a film that tells the assertiveness of the campus in taking action against perpetrators of sexual violence. This research method uses a descriptive qualitative method approach with the concept of fiction film design. The making of this film aims to influence other campuses out there in the process of cracking down on cases of sexual violence that occur within the scope of higher education. This film aims to influence other universities in handling cases of sexual violence on their campuses. Keywords: short film; film; production; sexual violence.